In vitro antagonism of Phytophthora capsici and Fusarium solani by bacterial isolates from Sarawak - Mohd Farith, Kota; Awang Ahmad Sallehin, Awang Husaini; Samuel, Lihan; Mohd Hasnain, Md Hussain; Hairul Azman, Ruslan (Malaysian Society of Microbiology, 2015)
Aims: Phytophthora capsici and Fusarium solani are common fungal pathogens causing severe diseases that lead to economic loss in pepper industry, especially in Sarawak. In response to the infections, chemical approach is more common; nevertheless, biological control is more favorable to control fungal pathogens. Biological control approach greatly reduces the problems associated with chemical applications and it restores balance of the natural environment. Here we present the ongoing work to study the action of antagonistic bacteria, Bacillus sp. and Pseudomonas sp., that produce volatile and non-volatile antifungal compounds against P. capsici and F. solani on pepper plants. Methodology and results: A total of seven bacterial candidates were isolated from different locations and tested for their antagonistic properties against P. capsici and F. solani in a dual culture assay and extracellular metabolite test. Extracellular hydrolytic enzymes production was also monitored and followed by genotypic indentification. Preliminary antagonism tests indicated that bacterial isolate Pep3 and Pep4 inhibit up to 50% of the growth of P. capsici and F. solani as compared to the control. Subsequent investigation on extracellular hydrolytic enzyme production revealed that both bacterial isolates are capable of secreting hydrolytic enzymes. Microscopic and genotypic analyses identified the bacterial isolates Pep3 as Bacillus amyloliquefaciens (KJ461444) and Pep4 as Pseudomonas pachastrellae (KM460937). Conclusion, significance and impact of study: B. Amyloliquefaciens (KJ461444) and P. pachastrellae (KM460937) inhibited the growth of P. capsici and F. solani thus reflecting the potential of the produced metabolites to be purified and used in combating plant pathogenic fungi.